The effects of early elective amniotomy on the length of labor and the condition of the fetus - Lynaugh, Kathleen H. (Journal of nurse-midwifery, 1980)
Amniotomy is done frequently for the purpose of shortening labor or applying an internal fetal monitor electrode. To determine if amniotomy is warranted as a routine procedure, a systematic review of literature on the subject was done. Studies pertaining to the length of labor showed either no consistent effect of amniotomy, or a shorter labor by a maximum of 61.5 min with early amniotomy. Studies pertaining to the condition of the fetus showed increased incidence of caput succedaneum, skull bone disalignment, and early decelerations with early amniotomy. A small controlled study showed decreased pH of newborns with early amniotomy. There was no significant difference in Apgar score or neurological examination of the newborn with early amniotomy. The author concluded that early amniotomy should be reserved for use with specific indications, and should not be used routinely in the low-risk parturient.